Highlighting gender issues at AASW6 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
Dr. Petra Abdulsalam-Saghir, Gender Specialist, Federal University of Agriculture, Nigera speaks of her expectations about the #AASW6 in meeting with Gender experts in Agriculture and rural development. The Forum for Agricultural Research in Africa (FARA) in collaboration with the Government of Ghana will convene the 6th Africa Agriculture Science Week from July 15-19 in Accra, a continental gathering of all stakeholders involved in African agriculture. Learn more: http://www.cgiar.org/calendar-events/ http://www.fara-africa.org/scienceweek/